Editorial (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The 20th anniversary of the AAS Revista/Latin American Journal of Sedimentology and Basin Analysis has arrived with exciting and challenging news. We can no longer say that this is a young journal and, through its maturity, new defies arrive and it is up to the whole community to be up to date with these, while valuing the founding spirit of the journal.Perillo (2005) in the first issue of the renewed journal suggested that LAJSBA was “our new reality”. We cannot agree more that it is now a reality. He also suggested that there were two challenges that the journal was facing in the future that included the generation of an online platform for the journal and the need of a leap into higher levels of international indexing. Now, after 8 years of that statement, we believe that we are in the path of consolidating this journal as a leading publication in sedimentology and basin analysis for the Latin American community, with a clear international projection.We can say that now the Latin American Journal of Sedimentology and Basin Analysis is a completely online-based journal, from the editorial process through the PPCT-Portal de PublicacionesCientíficas y Técnicas (CAICYT-CONICET, ppct.caicyt.gov.ar), to its online publication and storage in the SciELO platform (www.scielo.org.ar). The benefits of this online presence are in clear sight. Shorter submission- to-publication times in one side, and higher number of accesses to articles published in LAJSBA, which in turn translates into greater citation values, in the other. Another side advantage of this new virtual presence of LAJSBA is that, starting with this issue, an early online version of articles in press is now available at LAJSBA´s PPCT website (http://ppct. caicyt.gov.ar/index.php/lajsba/issue/archive). This reduces the publication times even more and allows full access to published material while articles wait for their definitive publication date.The success of the online initiative, something that was easy to anticipate considering the times we are now living, has encouraged the Asociación Argentina de Sedimentología (AAS) to take a step forward and discontinue the publication of the printed version of the journal after 19 years. Volume 20 will be the first published exclusively online andthis will allow the AAS to redirect the resources that the printed version of the journal consumed and eventually allow the publication of more articles per issue or increase the number of issues per volume without affecting the association´s finances in a drastic way. This is a long-lasting wish and some- thing that we were not able to accomplish in the first 20 years of the AAS Revista/LAJSBA initiative.